Casos de ensino: uma abordagem pedagógica para a formação de professores no ensino com mediação tecnológica no Amazonas - Oliveira, Carolina de Souza (2021)
The research presented the challenges faced by the teachers of the Centro de Mídias de Educação do Amazonas of the State Education Department with the possibility of minimizing / overcoming the demands for improvement through teacher training using the case instruction method. The achievement of this objective was addressed by the pursuit of listening, observing and structuring the narratives in and out of classroom experiences where teaching is mediated by digital technology in distant communities including the most remote cities from Manaus. The foundation of this qualitative research was directed at the literature, which is now scarce in Brazil on Teaching Cases, Problem Cases, Method of the case in teacher education in the area of education and recognition, even if succinct, of the cultural, geographical and contextual diversity of the state of Amazonas. As for the specific objectives for the development of scientific writing Centro de Mídias sought to identify the demands of teaching work, identifying the teacher training process, developing teaching cases contextualized to teaching practice and, applying the Teaching Cases in pedagogical workshops for teacher training at the same institution. As an educational product disseminated by digital e-book five teaching cases were prepared in the format of short cases, entitled How does the boat come from? Call whoever has the key, The storm is coming, Send the material and Class was 10. Also in the e-book there was a brief overview of those involved in the research, in the theoretical part as support to the participant and the trainer guidance on how to prepare to maximize the use of experience with this training method. The e-book was named Da Várzea a Terra Firme making an analogy to the research process and its changes during writing, but also to show how teaching cases and their educational objectives can establish learning communities and provide personal training advantage and professional. In addition, teaching cases as didactic material contribute to the improvement of teaching practice and have the effect of inspiring teachers with different perspectives, suggestions about a situation, providing a safe environment to idealize solutions or decision making.